2022
DOI: 10.3390/nano12203668
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic and Antibacterial Activity of CoFe2O4 Nanoparticles from Hibiscus rosa-sinensis Plant Extract

Abstract: Biogenic CoFe2O4 nanoparticles were prepared by co-precipitation and Hibiscus rosa sinensis plant leaf was used as a bio-reductant of the nanoparticle productions. The biosynthesized CoFe2O4 nanoparticles were characterized by XRD, FTIR, UV, VSM, and SEM via EDX analysis. The cubic phase of biosynthesized CoFe2O4 nanoparticles and their crystallite size was determined by XRD. The Co-Fe-O bonding and cation displacement was confirmed by FTIR spectroscopy. The presence of spherically-shaped biosynthesized CoFe2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Inbaneson et al proved the potential antibacterial activity of silver nanoparticles against E. coli isolated from UTIs [26]. In addition, cobalt ferrite, SnO2, and silver nanoparticles have been shown to have antibacterial efficacy against multidrug-resistant bacterial strains [11,15,16,18,27]. Another study showed the antibacterial activity of pure and co-doped (Fe & Ni) tin oxide nanoparticles against gram-positive and gram-negative bacteria [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inbaneson et al proved the potential antibacterial activity of silver nanoparticles against E. coli isolated from UTIs [26]. In addition, cobalt ferrite, SnO2, and silver nanoparticles have been shown to have antibacterial efficacy against multidrug-resistant bacterial strains [11,15,16,18,27]. Another study showed the antibacterial activity of pure and co-doped (Fe & Ni) tin oxide nanoparticles against gram-positive and gram-negative bacteria [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to their advantages, NPs can be employed to build and create various medication delivery systems. Organic and metallic nanoparticles and their combinations are examples of these systems for managing UTIs; the design of these NPs combines a matrix with antimicrobial properties and the incorporation of biologically active molecules such as antibiotics, plant extracts or proteins to boost the antimicrobial capacity of the new systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting ROS production will affect the level of antibacterial activity [58]. The balance will be disrupted when there is an increase in ROS in which the role of ROS is to inhibit protein function, cause DNA damage, and affect the level of lipid peroxidation which causes damage to cell membranes [59][60][61]. ROS production is determined by nanoparticles and depends on several factors such as size, morphology, shape, and release of metal ions [62,63].…”
Section: Antibacterial Activity Analysismentioning
confidence: 99%
“…34 CoFe 2 O 4 is widely used in wastewater treatment, 35 electrocatalytic applications (such as supercapacitors and overall water splitting), 36 Li-ion batteries, 37 the OER and ORR, 38 magnetic resonance imaging, 39 and photocatalytic and antibacterial applications. 40…”
Section: Introductionmentioning
confidence: 99%
“…34 CoFe 2 O 4 is widely used in wastewater treatment, 35 electrocatalytic applications (such as supercapacitors and overall water splitting), 36 Li-ion batteries, 37 the OER and ORR, 38 magnetic resonance imaging, 39 and photocatalytic and antibacterial applications. 40 In this study, ZIF-8@CoFe 2 O 4 composites were synthesized using a simple method (Scheme 1) and subsequently used as electrocatalysts for both the MOR and OER. XRD, XPS, FTIR, SEM, and HR-TEM were used to characterize the electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%